Corannulene and its complex with water: a tiny cup of water. Issue 22 (5th May 2017) - Pérez, Cristóbal; Steber, Amanda L.; Rijs, Anouk M.; Temelso, Berhane; Shields, George C.; Lopez, Juan Carlos; Kisiel, Zbigniew; Schnell, Melanie
Abstract : We report the results of a broadband rotational spectroscopic study of corannulene, C20 H10, all of its singly substituted 13 C isotopologues, and a complex of corannulene with one molecule of water. Abstract : We report the results of a broadband rotational spectroscopic study of corannulene, C20 H10, all of its singly substituted 13 C isotopologues, and a complex of corannulene with one molecule of water. Corannulene is a polycyclic aromatic hydrocarbon (PAH) with a curved structure that results in a large dipole moment. Observation of 13 C isotopic species in natural abundance allowed us to precisely determine the molecular structure of corannulene. The differences between the experimental C–C bond lengths correlate to the double-bond character predicted using Kekule's resonance structures. In the case of C20 H10 –H2 O, the water molecule is found to reside inside the bowl-like structure of corannulene. Our experimental and theoretical results indicate that the water molecule rotates freely around its C 2 axis and that dispersion interactions are the dominant contribution to the binding.